Research advances of erianin: Source, production, biological activities and pharmacological properties - Qinghe Qiao; Yihao Du; Lihang Xie (Pharmacological Research - Modern Chinese Medicine, 2022)
As the major bibenzyl compound extracted from Chinese traditional medicine Dendrobium chrysotoxum Lindl., erianin possesses plenty of biological properties including antibacterial, antiviral, anti-oxidant, anti-inflammatory, and especially anti-cancer activities with low toxicity and high efficiency. However, the natural source of erianin from Dendrobium species is limited and unsustainable. The methods of extraction, separation and chemical synthesis of erianin have been studied and developed. Meanwhile, biosynthesis also provides an alternative strategy for artificial synthesis of erianin. In addition, the previous studies also confirmed that the various biological activities of erianin were achieved with multiple mechanisms. This review summarized the source, production, biological effects, and action mechanisms, which would provide a theoretical basis and reference for industrialized production and clinical application of erianin.